The Birth of the Feminist Counter-public/Public Sphere in A Novel of a Young Girl by Draga Gavrilović (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Serbian feminist counter-public began to develop during the 1860s among the Serbian intellectuals in the Austro-Hungarian Empire, but it didn't deserve its name until the between-two-Wars period in the state frame of the Kingdom SHS/Yugoslavia (1918–1941). Like the public work of The United Serbian Youth and of several authors devoted to women's rights, the works of Draga Gavrilović have also been strongly marked by feminism. Her Girl's Novel represents a special kind of novel which simultaneously belongs to literature and to journalism. Since it was published during the 1889 as a serial novel (a specifically periodical genre), it was strongly connected to its context – journal Javor and Serbian (and Austro-Hungarian) press of the time – and was, therefore, directly involved in the (changes of) bourgeois public sphere of this 'dislocated' society. The novel was both a depiction of emerging feminist counterpublic and its active actor. By introducing the critique of bourgeois marriage and patriarchal norms, it appealed to (passive) women's reading public, and took part in the long process of forming the feminist public sphere as an alternative discursive arena or subaltern counter-public (Nancy Fraser). Through detailed representing of the characters' dialogues as public reasoning on the subjects of general interest, the novel showed the emergence of the public sphere in a way Habermas described it in his influential book The Structural Transformation of the Public Sphere. The specificity of the feminist public sphere seems to be in the new public places: a girl's bed/room, for example, becomes a public space and a public sphere when women start to discuss their interests in it.
Keywords: bourgeois public sphere; feminist counter-public; Draga Gavrilović; Girl’s Novel; periodical genres